Effects of a resiliency program on burnout and resiliency in family medicine residents. (September 2019) - Brennan, Julie; McGrady, Angele; Tripi, Jennifer; Sahai, Archit; Frame, Megan; Stolting, Alyse; Riese, Amy
Research has highlighted the prevalence of burnout in medical residents and the relative rarity of evidence-based structured programs to build resiliency. This was a controlled study of an 8-h program designed to increase resiliency and decrease burnout that focused on personal awareness, improving coping skills, building social connection, and maintaining balance. The project was approved by the institutional review board. Thirty-two family medicine residents signed the consent form. Structured assessment tools were administered to the intervention group at pre-program, immediately post-program and at one- and two-year follow-up. The control group completed the same pre- and post-assessments. Post-intervention comparison of the two groups demonstrated that the intervention group showed significantly lower scores in depersonalization and emotional exhaustion on the Maslach Burnout Inventory immediately after the program. There was no significant difference in the outcomes in year1 and year 2 follow-up. Residents evaluated the program positively. Resiliency programs can be incorporated into a family medicine residency and participants benefit by lowering indicators of burnout.